Nursing Leadership and Management Residency Proposal in Emergency Installation of Advent Bandung Hospital - Tambunan, Hamonangan; Silalahi, Harlena Rose; Sandy, Daniel; Simanjuntak, Samuel Maju (Devotion : Journal of Research and Community Service, 2025)
Emergency Department (ED) nurses are critical in delivering rapid, life-saving care, requiring continuous competency updates through training (e.g., BLS, ACLS) to enhance technical skills, decision-making, and stress management. However, delays due to triage inefficiencies, high patient volume, and staffing shortages undermine patient satisfaction, necessitating systemic improvements like Urgent Care integration. This study aims to (1) evaluate the impact of simulation-based training on ED nurse competency and (2) assess how Urgent Care implementation (e.g., digital queues, structured referrals) improves patient outcomes and workflow efficiency. A quasi-experimental design will compare EDs with and without interventions. Pre- and post-intervention data will be collected from 100 nurses (convenience sampling) via skills tests, stress metrics, and patient satisfaction surveys. Validity and reliability will be ensured through expert-reviewed instruments and Cronbach’s alpha (>0.7). Data analysis will use SPSS v.26 for t-tests and regression. Expected outcomes include improved nurse competency (20% faster decision-making), reduced wait times (30%), and higher patient satisfaction (15% increase). The study offers evidence-based strategies to optimize ED performance by integrating training innovations and systemic reforms, addressing both skill gaps and operational bottlenecks.